Clinical analysis of sirolimus therapy in children with refractory nephrotic syndrome - Nan Zhang; Le Jiang; Sanni Li; Yingying Zheng; Lei Dong; Yile Zhao (Renal Failure)
To investigate the clinical efficacy of sirolimus in treating children with refractory nephrotic syndrome, the clinical data for 22 children from the Children's Hospital of Hebei Province were analyzed retrospectively. There were 16 boys and six girls, and the treatment period was from September 2015 to April 2021. There were two patients with steroid-dependent nephrotic syndrome (SDNS), six patients with frequently relapsing nephrotic syndrome (FRNS), and 14 patients with steroid-resistant nephrotic syndrome (SRNS). All patients were defined as having refractory nephrotic syndrome. There were 12 patients (including nine SRNS patients and three FRNS patients) with minimal change disease (MCD), three patients (three SRNS patients) with focal segmental glomerular sclerosis (FSGS), one FRNS patient with mesangial proliferative glomerulonephritis (MsPGN), and six patients without a kidney biopsy. Compared with levels before sirolimus treatment, 24-hour urine protein (24-h UP), low-density lipoprotein cholesterol (LDL-C), urea (Ur) and serum creatinine (SCr) levels were significantly lower (all p < 0.05). Moreover, albumin (Alb) was significantly increased (p < 0.05), and there were no significant differences in total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), triglyceride (TG), immunoglobulin A (IgA), immunoglobulin G (IgG) or immunoglobulin M (IgM) (all p > 0.05) at the first follow-up. Sirolimus is effective as the first treatment of some children with refractory nephrotic syndrome, but its long-term efficacy and adverse reactions still require follow-up.